The educational role of nurses in the care of patients with chronic kidney disease - Pluta, Agnieszka; Budnik-Szymoniuk, Maria; Basińska-Drozd, Halina; Humańska, Marzena (Journal of Education, Health and Sport, 2017)
Chronic kidney disease affects about 11% of adults. This syndrome is an independent risk factor for cardiovascular diseases. Because of the progression of the disease and the consequences of renal replacement therapy, education of the patient is extremely important. Special role is attributed to nurses here. The purpose of this is to present the role of a nurse in the care of a patient with chronic kidney disease. Education is addressed both to the patient and to his loved ones. The development of centers specializing in the care of patients with kidney disease provides an opportunity to improve the quality of care, especially for patients with advanced disease.